2017
DOI: 10.1088/1475-7516/2017/07/018
|View full text |Cite
|
Sign up to set email alerts
|

The maximum sizes of large scale structures in alternative theories of gravity

Abstract: Abstract. The maximum size of a cosmic structure is given by the maximum turnaround radius -the scale where the attraction due to its mass is balanced by the repulsion due to dark energy. We derive generic formulae for the estimation of the maximum turnaround radius in any theory of gravity obeying the Einstein equivalence principle, in two situations: on a spherically symmetric spacetime and on a perturbed Friedman-Robertson-Walker spacetime. We show that the two formulae agree. As an application of our formu… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
49
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 41 publications
(52 citation statements)
references
References 80 publications
3
49
0
Order By: Relevance
“…It has been explicitly demonstrated that these approaches yield the same result for the CDM model [5], as well as for the BransDicke theory with a positive [36]. Let us now emphasize the new results we derive in the rest of this paper.…”
Section: Introduction and Overviewsupporting
confidence: 52%
See 3 more Smart Citations
“…It has been explicitly demonstrated that these approaches yield the same result for the CDM model [5], as well as for the BransDicke theory with a positive [36]. Let us now emphasize the new results we derive in the rest of this paper.…”
Section: Introduction and Overviewsupporting
confidence: 52%
“…For the explicit form of the above equation in the case of Brans-Dicke cosmology we refer the reader to [36]. Using Eq.…”
Section: W(t) = P E (T)/ρ E (T)mentioning
confidence: 99%
See 2 more Smart Citations
“…This is very similar to what happens in neutron stars where the mass-to-radius relation depends crucially on the poorly known equation of state [20], and observed pulsars with a mass at two solar masses rule out equations-of-state that predict a lower higher value for the star mass [21]. Then in [22] the authors considered dark energy models with a constant equation-of-state w, and soon after that the idea was further pursued in subsequent work applied to generic dark anergy models [23], Brans-Dicke theory [24] and DGP brane model [25]. Unfortunately, in novel cosmologies characterized by non-standard Friedmann-like equations it is highly non-trivial to see the implications of the prediction of the models regarding the maximum turnaround point, although a formula for R T may exist.…”
Section: Introductionmentioning
confidence: 99%